Experimental performance analysis of multipath TCP path characteristics in streaming UHD HEVC-dash over wireless networks - S. Wejin, J; Amca, H (International Journal of Engineering and Technology, 2018)
The multiple interfaces in modern devices today have given great promise in enhancing multimedia service delivery over wireless networks. However, the IP coupled nature of the TCP/IP protocol inhibits the simultaneous use of these interfaces. Multipath TCP (MPTCP), a protocol undergoing IETF standardization has been developed to simultaneously use multiple interfaces for service delivery over the Internet. In this paper, we studied the effect of MPTCP paths characteristics in streaming Ultra High Definition, High Efficiency Video Codec (UHD HEVC-DASH) while connected to multiple wireless access points. The findings though specific instead of general, reveal that under balanced and unbalanced network paths, MPTCP offers good Quality of Experience (QoE) compared to SPTCP. However, with variability in latency, and packet loss between paths, MPTCP underperforms compared to SPTCP in terms of video buffering in the unbalanced network case, and high packet retransmission rate in either balanced or unbalanced network paths.Â Â